FRI0531 Dual energy x-ray absorptiometry testing in elderly men with prostate cancer initiating androgen deprivation therapy reduces subsequent fracture risk. (15th June 2017) - Suarez-Almazor, ME; Salazar, GM Cabanillas; Zhao, H; Shi, B; Kim, J; Elting, L
Abstract : Background: Androgen deprivation therapy (ADT) is a mainstay therapy for prostate cancer, and a risk factor for bone mineral density (BMD) loss and fractures. Despite this risk, few patients undergo measurement of BMD when initiating ADT. Conceivably, screening for bone loss could lead to identification of patients at risk, and to implementation of bone conserving therapy (BCT), and subsequent decrease in fracture risk. Objectives: To evaluate the utilization of Dual Energy X-ray Absorptiometry (DXA) testing for measurement of BMD in elderly patients with prostate cancer initiating treatment with ADT, and the effects of testing on subsequent fracture risk. Methods: We conducted a population-based retrospective cohort study using the Surveillance, Epidemiology, and End Results (SEER) and Texas Cancer Registry (TCR) databases linked to Medicare claims. Medicare is the United States national health insurance program for individuals aged 65 and older. We identified all men over 66 years old with a diagnosis of prostate cancer who received ADT. We identified claims for DXA within 12 months prior, and 12 months after ADT initiation. We assumed that if patients had DXA testing in the year before ADT, this would not be repeated. We then ascertained claims for fractures during follow-up after ADT onset, comparing those who had undergone DXA with those who had not. Statistical analysis included multivariate logistic regression adjusting for demographic and clinical variables. Results: The cohort included 36, 739 men with prostate cancer treated with ADT; 48.3% were over 75 years of age and 75% were white. Only 5.2% of the patients underwent DXA within the window of evaluation. Men were more likely to have DXA id the were white vs. African American, and if the lived in census tracts with higher socio-economic status. When comparing the incidence of fractures, 11.3% of those who underwent DXA had a fracture, compared to 19.4% of those who did not undergo DXA (p<0.0001). In the multivariate model an increase in the odds for a fracture was associated with older age, being White, having a prior history of osteoporosis or fracture, were evaluated with DXA.A decrease in the odds for a fracture was associated with having undergone DXA testing (0.70; 95% CI 0.61 – 0.80). Conclusions: Very few patients with prostate cancer starting ADT undergo DXA despite being at increased risk of fracture. DXA use was associated with socioeconomic status. Our results show that patients who underwent DXA were significantly less likely to have a fracture. Our findings suggest that DXA should be performed in all patients with prostate cancer initiating ADT. References: V. B. Shahinian, et al. Risk of Fracture After Androgen Deprivation for Prostate Cancer. N Engl J Med, 352:154–164, 2005. Philip J. Saylor, Donald S. Kaufman, M. Dror Michaelson, Richard J. Lee, and Matthew R. Smith. Application of a Fracture Risk. Algorithm to Men Treated With Androgen Deprivation Therapy for Prostate Cancer. J Urol. 2010 June; 183(6): 2200–2205. Acknowledgements: To our patients. Disclosure of Interest: None declared